LAMB3 is associated with disease progression and cisplatin cytotoxic sensitivity in head and neck squamous cell carcinoma. Issue 3 (March 2019) - Liu, Lihua; Jung, Seung-Nam; Oh, Chan; Lee, Kyungmin; Won, Ho-Ryun; Chang, Jae Won; Kim, Jin Man; Koo, Bon Seok
Abstract: Objectives: Laminin subunit beta-3 (LAMB3) is a major component of the basement membrane zone. In our study, we investigated the role of LAMB3 in head and neck squamous cell carcinoma (HNSCC) progression and its clinical implication as a prognostic biomarker. Materials and methods: A retrospective analysis of 100 patients with HNSCC who had undergone curative surgery from 1999 to 2011 was performed. We evaluated LAMB3 expression by immunohistochemistry and its associations with clinicopathological characteristics and survival. For functional in vitro analyses, cell proliferation, migration, and invasion and western blot assays were performed following LAMB3 suppression. In addition, the role of LAMB3 in cisplatin-induced cytotoxicity was clarified by measuring cell proliferation. Results: LAMB3 expression was up-regulated in HNSCC cell lines and patient tissues. High LAMB3 expression was significantly associated with positive lymph node metastasis (odds ratio: 6.316; P < 0.001) and poor prognosis in patients with HNSCC. LAMB3 suppression reduced cell migration/invasion via down-regulation of epithelial-to-mesenchymal transition-associated proteins (Vimentin and Slug). Moreover, LAMB3 suppression increased cisplatin cytotoxicity in HNSCC cells. Conclusion: Our findings indicate that LAMB3 may be used as a prognostic biomarker in HNSCC and support that LAMB3 silencing could induce the sensitivity of anti-cancer drugs such as cisplatin.